PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP AGRESIVITAS PAJAK DENGAN KEPEMILIKAN KELUARGA SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Hasian Purba (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
The purpose of this study are as follows: 1) Find empirical evidence on the influence of Corporate Social Responsibility (CSR) on Tax Aggressiveness; 2) Find empirical evidence of family influence on tax aggressiveness; 3) Find empirical evidence of family closeness to corporate social responsibility to tax aggressiveness. The type of research used in this study is associative casual research (causal assosiative research). The population used in this study is all non-financial companies listed on the Indonesia Stock Exchange period 2012-2015. Sampling in this research is done by using probability sampling method with sampling technique using random sampling. The analytical method used for. Moderate Regression Analysis. The results showed, 1) Disclosure of negative Corporate Social Reporting on Tax Aggressiveness; 2) Family Ownership has a positive and significant impact on Tax Aggressiveness; 3) Family Ownership may moderate the relationship between Disclosure of Corporate Social Responsibility and Tax Aggressiveness in a negative direction.